Please answer this question.

9 .     I f   a   +   b   =   2 c ,   t h e n   t h e   v a l u e   o f   a a   -   c + c b   -   c   i s   e q u a l   t o   w h e r e   a     b   c   ( A )   -   1                                                                 ( B )   1 ( C )   0                                                                           ( D )   1 2

Dear student
Given: a+b=2c a=2c-b      ...(1)a=c+c-ba-c=c-b     ..(2)Consider,aa-c+cb-c=a-(b-c)+cb-c    using 2=-ab-c+cb-c=-a+cb-c=-2c-b+cb-c    [using 1]=-2c+b+cb-c=b-cb-c=1
Regards

  • 0
What are you looking for?